The Implementation of Strict Liability Doctrine in Environmental Crimes Based on New Criminal Code - Semuel Haning; Wilsa Wilsa; Vegitya Ramadhani Putri (Journal of Mandalika Social Science, 2026)
Environmental crimes continue to increase despite the existence of criminal sanctions, indicating limitations in conventional fault-based criminal liability systems. This research aims to analyze the implementation of strict liability doctrine in environmental crimes under the New Criminal Code and its significance for strengthening environmental criminal accountability. The study employs normative legal research using a library research method through the examination of books, journals, legal documents, prior studies, and other relevant scientific literature. The data consist of primary legal materials concerning environmental criminal law and secondary materials related to strict liability doctrine, environmental crimes, and criminal law reform. Data were analyzed using content analysis to identify legal patterns, conceptual relationships, and normative developments. The findings indicate that strict liability doctrine strengthens environmental law enforcement by simplifying evidentiary burdens, enhancing preventive legal functions, and supporting sustainable environmental governance. Consequently, the New Criminal Code reflects a progressive approach toward more effective and sustainability-oriented environmental criminal protection.